Solidifying Cathode–Electrolyte Interface for Lithium–Sulfur Batteries - Wang, Wen‐Peng; Zhang, Juan; Chou, Jia; Yin, Ya‐Xia; You, Ya; Xin, Sen; Guo, Yu‐Guo (Advanced energy materials, 2021)
Lithium–sulfur (Li–S) batteries, with their distinct advantages in energy output, cost, and environmental benignancy, have been recognized as one of the most promising candidates for near‐future energy storage markets. However, the energy storage technology based on Li–S systems, even at the single cell level, is far from commercialization. The implementation of the technology is hindered by unstable electrochemistry at the electrode–electrolyte interface, especially the cathode–electrolyte interface. In cases where the cathode builds a solid–liquid interface with the electrolyte, strong interactions between discharge intermediates of S and solvent molecules of the liquid electrolyte lead to continuous loss of active S species from the cathode to the anode through an electrochemical shuttle process, and hampers the cycling performance of the battery. By solidifying the cathode–liquid interface, the polysulfide–solvent interaction is expected to be alleviated and the Li–S electrochemistry improved. In this Progress Report, the strategies to build a solidified cathode–electrolyte interface in liquid, quasi‐solid‐state and all‐solid‐state Li–S systems are summarized, and the fundamentals of charge transfer and chemical evolutions at the interface are discussed. With these discussions, the rational interfacial design of Li–S batteries is elucidated, toward optimal storage performance and operational durability. This progress report surveys the frontier research on solidifying the cathode–electrolyte interface, a promising strategy for addressing the polysulfide crossover issues of Li–S batteries. In addition to the summary of recent advancements, the fundamental knowledge, challenges, and prospects of various types of solidified interfaces are discussed to shed light on the rational design of authentic Li–S batteries.